PEMANTAUAN KASUS PENYEBARAN COVID-19 BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK REACT JS DAN API - Tri Sulistyorini; Erma Sova; Rafli Ramadhan (Jurnal Ilmiah Multidisiplin, 2022)
The world has been attacked by the pandemic of coronavirus, starts from 2019 until this day, 2022. Coronavirus was detected in Indonesia started from 2020, specifically on March, 2020. The coronavirus or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the virus which attacks human’s respiratory system. It is also known as COVID-19. The virus may cause mild illnesses of human’s respiratory system, severe lung infections, and even death. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is categorized as the new infectious disease to human. The virus attacks anyone, such as elderly, adult, children, toddler, pregnant women, and breastfeeding mothers. Utilization of information technology that continues to develop can be felt in various fields. Such as the fields of education, government, health, social culture and so on. Information about COVID-19 is always needed by the people of Indonesia, even abroad. Utilization of this website-based technology can help the public in obtaining up to date information. Website application built using React JS framework and API. According to the problems experienced now, a website was created to monitor and provide accessible information to the public regarding the spread of COVID-19 virus cases in Indonesia and the entire world as well. People could approach the website called Covices which was created in programming languages, such as React Js and API.